Ultrasonography Findings in Acute Appendicitis: A Case Study - Angelina Vanessa Prasethio; Aldwin Wiranata Fam; Ayen Giovina; Hendi Fuki Lukmanta; Ingrid Anjani; Kadek Ayu Sri Purniawati; Komang Intania Putri Pelangi; Mutia Utami Ariani; Pinkan Al Shabrina; Mathias Rusli (Rumah Sakit Unggul Karsa Medika, 2022)
Acute appendicitis is one of the most common diagnosis suspected in patients with acute abdominal pain. Classic symptoms such as right iliac fossa pain, anorexia, nausea, constipation, and vomiting only occur in 50% of cases. Thus, other diagnostic modalities are still needed to help doctors conclude the definitive diagnosis that lead to prompt treatment. Ultrasound examination of the abdomen could be good choice since it is relatively faster, cheaper, and quite accurate in diagnosing appendicitis. This study presents an example of ultrasonography examination of patient with abdominal pain suspected of appendicitis. Ultrasound imaging showed echoic inflamed fat with appendix diameter of 13,1 mm indicates acute inflammation of appendicitis. Dilated appendix which is more than 6 mm in size was one of the supportive sign to propose appendicitis. This finding was in line with the patient’s signs and symptoms, thus acute appendicitis was diagnosed. The patient went to surgery and appendectomy was performed. This study showed us how abdominal ultrasound could add diagnostic value to diagnose acute appendicitis.